The Angels Won't Help You - Bowker, Matthew (punctum books, 2022)
The Angels Won't Help You is a book about the uniqueness and primacy of help, particularly in relation to care, love, and caritas. It relies heavily on psychoanalytic and philosophical accounts of help and care and finds that help requires the establishment of a real relationship between persons, where help is given and received in a transitional space that is collapsed by care, unity, or love, which are mental constellations that, while profound, remain within the individuals involved. It contains reflections, memoir, and prose poetry, with an emphasis on psycho-philosophical examinations of help. In trying to understand help, especially in the ways that it is not a synonym for care, Bowker turns to diverse sources and topics, including treatments of children in a helpless world, as featured in the literature of Kathy Acker and Jerzy Kosiński, a first-person account of help in psychiatric hospitals, an analysis of the phenomenon of Japanese hikikomori ("shutting oneself in"), anxiety and helplessness, an exploration of the nature of help and helplessness in Wilfred Bion's "Attacks on Linking," a rethinking of trauma in light of the circuital structure of the self, and more. *** Put differently, The Angels Won't Help You is a cruel helpless hopeless book raised in Texas roped ridden waddled clowned it developed catastrophic methods of coping. Angels' mama split her tongue and hissed her words like silent / soldier / crisis in the torment of her sunken trailer in the summer where Angels practiced lighting cigarettes with her eyes fetching fireflies making tinctures of dead tissue becoming extraordinarily promiscuous. Angels' nature was to hide in dark places to ride with abandon to sink in the spurs to gnash silver teeth to kick up tipped boots ruining every square dance. Angels, you make me need like a choke rope dream of being sick from head to foot. You are the petaled froth on every steep lapel. You are original and dilapidated depilatory and inflationary ovulary and delusional. O Angels, the scholars will say I failed to know you address you presage you protect you protest you, but we know the truth.